Rock Physics Modelling for Estimating the Quality of Reservoir Tight Sand in Bintuni Basin, West Papua, Indonesia - Dona Sita Ambarsari; S. Winardhi (Jurnal Geofisika, 2018)
Permeability is a key to determine the quality of reservoir. Reservoir quality can be dened as the ratio between permeability and porosity of a rock. Besides, permeability is not in uenced by porosity solely, there are otherfactors which aect the value of the permeability of a rock. One of them is aected by the pore structure, which includes turtuosity, surface area, and grain size. To determine how much these factors aect the permeability of a rock, it takes an elastic parameters that can be an indicator of the quality reservoir e.g pore space stiness and critical porosity.Primary data such as petrophysics, XRD data, and permeability are used as input data to determine the quality of reservoir. By using Zimmerman's equation and Nur's model, we will get the value of pore space stiness and critical porosity at each point. The combination of rock quality equation derived from Kozeny Carman's with elastic parameters as indicators produces qualitative rock quality identification. Results of this study is able to show that the pore space stiffness and critical porosity can represent turtuosity, surface area, and grain size of a rock which lead to the determination of rock quality. The method proposed in the present study demonstrated an excellence reservoir quality prediction based on the relation between petrophysical parameters with elastic parameters.